EVALUASI PENGGUNAAN ANTIBIOTIKA PROFILAKSIS DARI ASPEK KETEPATAN JENIS, WAKTU DAN DURASI PEMBERIAN PADA PASIEN INSTALASI BEDAH SENTRAL SEBUAH RUMAH SAKIT SWASTA DI YOGYAKARTA - Dimas Adhi Pradana; Iwan Dwiprahasto; Satibi Satibi (Jurnal Ilmiah Farmasi, 2009)
ABSTRACTSurgical site infection is one of surgical infection that frequently happened in hospital sothat the use of antibiotic prophylaxis must be safe. The research was conducted to know incidenceof adverse event at usage of antibiotic prophylaxis in surgery installation. We use concordancesheet of antibiotic prophylaxis either from accuracy aspect of the drug type, administration time,duration of usage. Result analysis in the form of calculation relative risk of usage of antibioticdissected pre prophylaxis to risk the happening of surgical site infections cases. Result thisresearch show that relative risk value of usage of antibiotic to case of infection of operation hurtevaluated from inaccurate of type antibiotic 1,12 ( CI 95 %: 0,138-9,1), inaccurate aspect of gift time5,8 ( CI 95 % : 1,024 - 32,86) and from inaccurate aspect of duration of gift 3,21 ( CI 95 % : 1,043 -9,9).Keywords: antibiotic prophylaxis, surgical site infections, relatives risk